Auditoría financiera a la Cooperativa de Transportes Patria, periodo 2017 para determinar la razonabilidad de los estados financieros” - Verónica Alexandra, Tuquinga Ausay (2021)
The main objective of this research project is to execute the Financial Audit to the Cooperativa de Transportes Patria period 2017, to determine the reasonableness of the financial statements. In the development of the research, the referential framework containing the statement of the problem, objectives and reason for the audit development, as well as the theoretical framework where research related to the subject were considered and the main contents referring to the financial audit were conceptualized. In the methodology, the deductive method was used, which was fundamental to develop the research, the type of investigation was documentary, which facilitated the analysis of all the paperwork of the union. Finally, the audit phases were developed; they began with the planning phase in which a visit was made to the Cooperative to get the general data and make a diagnosis; During the execution, the selected components were evaluated through the internal control questionnaire and other paperwork, where findings were determined, and in the results communication phase, a final report was made with a clean opinion on the reasonableness of the financial statements of the company. Cooperativa de Transportes Patria, since the differences found during the audit do not exceed the materiality established by the auditor.